Imaging in Uncommon Uterine Malignancies - Agarwal, Divij; Manchanda, Smita; Aggarwal, Ankita; Dhamija, Ekta; Singhal, Seema; Meena, Jyoti (Journal of Gastrointestinal and Abdominal Radiology, 2025)
This review provides a comprehensive overview of the classification and imaging characteristics of uncommon uterine malignancies, guided by the latest World Health Organization classification of female genital tumors (fifth edition, 2020). We discuss the imaging features of rare entities, including leiomyosarcoma, endometrial stromal sarcoma, stromal tumor of uncertain malignant potential, carcinosarcoma, adenosarcoma, perivascular epithelioid cell tumor, and uterine tumors resembling ovarian sex-cord tumors. Although these malignancies often present with nonspecific and overlapping imaging appearances, advances in cross-sectional imaging (particularly magnetic resonance imaging [MRI]) play a critical role in tumor detection, characterization, staging, and treatment planning. Key MRI findings, such as signal intensity patterns, enhancement characteristics, and diffusion-weighted imaging, can help to narrow differential diagnoses and inform management strategies. By emphasizing distinctive imaging features and their clinical relevance, this review aims to enhance diagnostic confidence and multidisciplinary care for patients with these challenging uterine malignancies.
Keywords: uterus; MRI; sarcoma; mesenchymal; malignancy; leiomyosarcoma; leiomyomas; endometrial stromal sarcoma; carcinosarcoma; STUMP